The Grammaticalization of Down - Sądej, Kinga (Studia Anglica Posnaniensia, 2009)
The present paper discusses the grammaticalization of down, focusing on when the process began and how it developed. The ultimate origin of down, both the adverb and the preposition, should be traced back to OE dūn ‘hill, mountain’, whose frequency of occurrence in Old English is comparable to those of beorg and munt. By means of grammaticalization the noun dūn came to function as an adverb meaning ‘in a descending direction; from above, or towards that which is below; from a higher to lower place or position’ already in Late Old English. The adverbial meaning of dūn is derived from OE of dūne ‘off the hill or height’ (glossing L de monte). The expression of dūne gave rise to the adverb adūne which was aphetized to dūn (doun, down) at the beginning of the twelfth century. By analysing the textual evidence, the present investigation is an attempt at verifying this date.